1992
DOI: 10.1136/jnnp.55.12.1177
|View full text |Cite
|
Sign up to set email alerts
|

Material-specific memory loss in probable Alzheimer's disease.

Abstract: This study extends previous work analysing functional dissociations occurring in patients with Alzheimer's disease (AD) by demonstrating that material-specific memory loss is common. The pattern of neuropsychological dysfunction in 191 patients with probable AD was examined and 13% presented with material-specific memory loss. Thirteen patients had impaired immediate verbal recall, but normal non verbal recall and 12 had impaired non verbal recall and normal verbal memory. These patterns appeared to be related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
8
0
2
Order By: Relevance
“…Other studies have demonstrated that the secondary memory deficit in AD could be distinguished from alterations in primary or working memory (Becker, 1988; Becker, Lopez, & Wess, 1992), all of which suggest that our understanding of the cognitive systems affected in AD need to include a breakdown in executive functions very early in the process. More recent studies have also found impaired executive functions in AD patients such as difficulty developing logical strategies and executing complex predetermined plans on the Zoo Map test (Allain et al, 2007; Piquard et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that the secondary memory deficit in AD could be distinguished from alterations in primary or working memory (Becker, 1988; Becker, Lopez, & Wess, 1992), all of which suggest that our understanding of the cognitive systems affected in AD need to include a breakdown in executive functions very early in the process. More recent studies have also found impaired executive functions in AD patients such as difficulty developing logical strategies and executing complex predetermined plans on the Zoo Map test (Allain et al, 2007; Piquard et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, he had nor mal scores on nonverbal tasks, but was abnormal on ver bal memory tasks. This dissociation of memory abilities has been noted in AD patients [33], and suggests a relative preservation of the right temporal lobe functions. How ever, neither neuroradiological studies nor subsequent neuropathological analysis revealed structural asymme try.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MCI with isolated executive deficits has been reported to be associated with cerebrovascular disease and a predictor of vascular dementia. MCI subjects with multiple disease processes that can affect cognition can progress to AD, 18 and not all AD patients have memory loss at initial presentation; 25 usually, mild nonmemory function deficits are difficult to detect with brief cognitive evaluations (Case 7-1). 24 The purpose of these criteria was to identify subjects in the pre-AD state, and they require that patients with MCI must have impairments in one or more cognitive domains.…”
Section: Criteria Yearmentioning
confidence: 99%